2020
DOI: 10.3389/fendo.2020.552054
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Maternal Lifestyle and Risk of Metabolic Syndrome in Offspring—A Cross-Sectional Study From China

Abstract: BackgroundThe prevalence of MS among children and adolescents continues to rise, which has become an escalating serious health issue worldwide. It had been reported that maternal current lifestyle had a strong independent correlation with offspring health. However, it is not clear whether comprehensive lifestyle of mother has an impact on the MS risk in offspring and the role of offspring’s lifestyle in it.Methods and ResultsWe included 4,837 mother-child pairs from a multi-centered cross-sectional study condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…Consistent with our findings, Simonetta ( 42 ) also demonstrated the significant efficacy of lifestyles modification on children blood pressure. These results were also supported by another Chinese study ( 43 ), which reported that the risk of offspring metabolic syndrome was lower in those who had more ideal lifestyle factors. Moreover, given that there is still a p for trend in paternal age in the favourable group, conclusion regarding the offset effect of lifestyle on association of paternal age should be drawn with caution.…”
Section: Discussionsupporting
confidence: 72%
“…Consistent with our findings, Simonetta ( 42 ) also demonstrated the significant efficacy of lifestyles modification on children blood pressure. These results were also supported by another Chinese study ( 43 ), which reported that the risk of offspring metabolic syndrome was lower in those who had more ideal lifestyle factors. Moreover, given that there is still a p for trend in paternal age in the favourable group, conclusion regarding the offset effect of lifestyle on association of paternal age should be drawn with caution.…”
Section: Discussionsupporting
confidence: 72%
“…In previous studies conducted in children and adolescents, maternal weight, smoking, and alcohol consumption were related to offspring obesity [42] and metabolic syndrome [43,44]. In the present study, maternal healthy lifestyle (characterized by a healthy body mass index, high-quality diet, regular exercise, low screen time, and no smoking) was associated with adherence to MedDiet in offspring, which emphasized the importance of maternal lifestyle, and suggested a combined effect of maternal and offspring lifestyle on child and adolescent diet.…”
Section: Discussionmentioning
confidence: 94%
“…The term “health lifestyle” pertains to the collective patterns of health-related behavior that individuals adopt based on the choices within the context of their life circumstances. 34 In order to comprehensively assess the health lifestyle of the participants, this study incorporated five commonly utilized behavioral indicators from previous researches, 19 , 35 , 36 namely smoking status, alcohol consumption, sleep duration, physical examination attendance, and physical activity. Following the scoring methodology employed in previous researches, this study assigned scores to various manifestations of these five health-related behaviors, which reflected their degree of alignment with established public health recommendations.…”
Section: Methodsmentioning
confidence: 99%